Effects of ice accretion on the aerodynamics of bridge cables. Issue 138 (March 2015) - Demartino, C.; Koss, H.H.; Georgakis, C.T.; Ricciardelli, F.
Abstract: Undesirable wind induced vibrations of bridge cables can occur when atmospheric conditions are such to generate ice accretion. This paper contains the results of an extensive investigation of the effects of ice accretion due to in-cloud icing, on the aerodynamic characteristics of bridge hangers and stay cables. The aim of this paper is twofold; first, it was investigated the ice accretion process and the final shape of the ice accreted; then the aerodynamics of the ice accreted bridge cables was characterized, and related to the ice shape. Different climatic conditions, i.e. combinations of temperature, wind speed and yaw angle of accretion, were reproduced in a climatic wind tunnel, giving rise to different types of accretion. These were chosen such to generate the most common natural ice formations expected to produce bridge cable vibrations. A description of the geometric characteristics of the ice accretions is given in the paper. Only for the bridge hanger case, a short description of the evolution of the ice accretions is given. The aerodynamic force coefficients were then measured with varying yaw angle, angle of attack and wind speed, and are presented and discussed in the paper; these are found to be significantly affected by the characteristics of the ice accretion.